KLASIFIKASI AYAT-AYAT AL-QUR’AN YANG MEMUAT KONSEP OPERASI BILANGAN SERTA INTEGRANYA DENGAN AGAMA ISLAM - Putra, Imam Setiadi (FiTUA: Jurnal Studi Islam, 2020)
The development of mathematics is inseparable from the role of the books revealed to the messengers of Allah, especially we are the Holy Qur'an. The emergence of the Qur'an has changed the whole structure of human life so that humans are more developed and advanced in science and technology, and even many Islamic figures play a role in the development of mathematics. This study aims to classify the Qur'anic verses which contain number operations and their integration with the Islamic religion. This research is qualitative research using the literature study method. The literature used is the result of various thesis writings, articles, and verses of the Qur'an. The data collected in the study are collected, analyzed, and presented in accordance with the research objectives. The results of this study are the classification of the Qur'anic verses that contain the concept of number operations, namely 1) Addition Operations contained in Q.S. Al Baqarah (2): 196 and 234, Q.S. Al A’raf (7): 142 and Q.S. Al Kahf (8): 25; 2) Reduction Operations are contained in Q.S. Al Qasas (28): 27, Q.S. Al Ankabut (29): 14 and Q.S. Al Muzzammil (73) 3-4; 3) Multiplication operations are found in Q.S. Al Baqarah (2): 261 and 4) Operation of division is in Q.S. Al Muzzammil (73): 20. Integration of number operations with the religion of Islam lies in the attitude of honesty, simple attitude and fair attitude